THU0482 Gene Expression Profiling of Whole Blood Samples of TRAPS Patients Shows Insight into the Molecular Pathogenesis of TRAPS and Response to Canakinumab Treatment. (10th June 2014) - Nirmala, N.; Torene, R.; Lachmann, H.; Obici, L.; Meini, A.; Tormey, V.; Caorsi, R.; Baeriswyl, L.; Affentranger, U.; Starck-Schwertz, S.; Letzkus, M.; Hartmann, N.; et al.
Abstract : Background: TNF receptor-associated periodic syndrome (TRAPS) is an autoinflammatory disease causing unprovoked fevers, myalgia, abdominal pain, rash, headaches, and, in severe cases, AA amyloidosis. It is an autosomal dominant condition resulting from variants in the TNF super family receptor 1A ( TNFRSF1A ) gene. 1 A hallmark of TRAPS is a huge activation of the inflammatory response in the absence of autoantibodies or antigen-specific T-cells. 1 Canakinumab (CAN) is a high-affinity, fully human, selective, anti-IL-1β monoclonal antibody, developed for the treatment of autoinflammatory diseases. 2 Objectives: To determine whether gene expression in whole blood can support a molecular mechanism for the activity of CAN in TRAPS patients (pts). Methods: Twenty pts with active TRAPS received open-label CAN 150mg sc/month for 4 months in an efficacy and safety study. These pts were assessed at Day 15 for response by physician global assessment (PGA) disease activity scale. Whole blood was collected at baseline, Day 15 and Day 113 from 19 of these pts and 1 sample each from 19 untreated age-matched healthy volunteers for analysis of gene expression levels by microarrays. Results: All 20 pts showed improvements in PGA score (Figure 1 -left). Gene expression profiles of these pts were altered by treatment with CAN. Forty-six differentially expressed genes showed a >2-fold change after treatment with expression levels that shifted towards that of healthy volunteers. The disease-causing gene ( TNFRSF1A, Figure 1-right), drug target gene ( IL-1β ), and other inflammation related genes (e.g., MAPK14 ) were downregulated after treatment and several inflammation related pathways were evident among the differentially expressed genes. Many of the high confidence differentially expressed genes had expression levels that correlated with neutrophil count, however, neutrophil count alone could not account for the expression differences observed. Conclusions: Altogether, the gene expression data support a model in which CAN increases neutrophil apoptosis and reduces pro-inflammatory signals through its inhibition of IL-1β. CAN is able to reverse the overexpression of several genes associated with inflammatory response, including IL-1. Interestingly, IL-1 blockade normalized the overexpression of the disease-causing gene, TNFRSF1A, at the RNA level, suggesting a direct impact on its main pathogenic mechanism. References: McDermott MF, et al. Cell 1999; 97(1):133–44. 2. Lachmann HJ, et al. J Exp Med.2009; 206(5):1029–36. Disclosure of Interest: : N. Nirmala Employee of: Novartis Institutes of Biomedical Research, R. Torene Employee of: Novartis Institutes of Biomedical Research, H. Lachmann Grant/research support: Novartis, Celtic, L. Obici Consultant for: Consultation fees from Pfizer Pharmaceuticals, A. Meini: None declared, V. Tormey: None declared, R. Caorsi: None declared, L. Baeriswyl Employee of: Novartis Institutes of Biomedical Research, U. Affentranger Employee of: Novartis Institutes of Biomedical Research, S. Starck-Schwertz Employee of: Novartis Institutes of Biomedical Research, M. Letzkus Employee of: Novartis Institutes of Biomedical Research, N. Hartmann Employee of: Novartis Institutes of Biomedical Research, K. Abrams Shareholder of: Novartis, Employee of: Novartis Pharmaceutical corporation, M. Gattorno Grant/research support: Novartis, SOBI, Speakers bureau: Novartis, SOBI DOI: 10.1136/annrheumdis-2014-eular.1503